An injectable self-healing hydrogel-cellulose nanocrystals conjugate with excellent mechanical strength and good biocompatibility. (1st November 2019) - Du, WenBo; Deng, Amin; Guo, Juan; Chen, Jian; Li, Huaming; Gao, Yong
Graphical abstract: Nanocomposite hydrogel derived from diol-containing polymer chains grafted cellulose nanocrystals and phenylboronic acid-containing copolymers showed excellent self-healing, injectability, stimuli-responsiveness and biocompatibility together with good mechanical strength. Highlights: A novel method for the construction of CNC-reinforcing hydrogel was demonstrated. The constructed NC hydrogel exhibited good self-healing and injectability. The constructed NC hydrogel exhibited excellent mechanical strength. The constructed NC hydrogel exhibited responsiveness and good biocompatibility. Abstract: In this work, a novel strategy for the construction of injectable self-healing nanocomposite (NC) hydrogels dominated by reversible boronic ester bonds was demonstrated. Specifically, NC hydrogels were constructed by the solution-mixing of N, N -dimethylacrylamide- stat -3-acrylamidophenylboronicacid statistical copolymers (PDMA- stat -PAPBA) and poly(glycerolmonomethacrylate) (PGMA) chains grafted cellulose nanocrystals (CNC- g -PGMA). Rheology analysis indicated the as-constructed NC hydrogel displayed about 7-fold increase in the storage modulus with a low CNCs loading level of 1.43 wt% in comparison with PGMA/PDMA- stat -PAPBA hydrogel without CNCs. Furthermore, the mechanical strength of the CNC- g -PGMA/PDMA- stat -PAPBA hydrogel was far superior to that of its PGMA/PDMA- stat -PAPBA/CNCs hydrogel counterpart, in which PGMA chains were not covalently grafted on the surfaces of CNCs. Due to reversible boronic ester bonds cross-linking networks, CNC- g -PGMA/PDMA- stat -PAPBA NC hydrogel exhibited excellent self-healing and injectable properties as well as pH/glucose responsive sol-gel transitions. Good biocompatibility was also demonstrated through in vitro cytotoxicity tests.